Партнерство инженерных вузов и предприятий. Опыт ТУСУР; Инженерное образование; № 32 - Троян П. Е. Павел Ефимович; Сахаров Ю. В. Юрий Владимирович; Жидик Ю. С. Юрий Сергеевич; Чистоедова И. А. Инна Анатольевна (2022, 2022)
Заглавие с титульного листа